Peran Tim Kontekstual Dalam Pelayanan Anak Suku Sunda: Upaya Memperkenalkan Isa Al-Masih Sebagai Satu-Satunya Jalan Keselamatan - Romita Romita; Jose Samaloisa; Markus Landena (Pusat Riset dan Inovasi Nasional, 2024)
This article discusses the changes experienced by Sundanese children during puberty and the important role of the gospel spirit companion in guiding them. Sundanese society has unique and interesting characteristics that must be observed in its spiritual growth and understanding of the concept of salvation. Although Sundanese society already has good morals and a high spirit of tolerance, to achieve soul salvation according to the concept of Christian salvation, faith in Jesus Christ is needed. Unfortunately, children are often neglected in evangelism, and the lack of service to them is a problem that must be overcome. Therefore, the